EFEKTIVITAS PELAKSANAAN UJIAN NASIONAL TINGKAT SEKOLAH MENENGAH ATAS NEGERI OLEH DINAS PENDIDIKAN DAN PENGAJARAN KOTA PALU PROVINSI SULAWESI TENGAH - Nursyam, Nursyam (Katalogis, 2017)
The goal of this research is to investigate and analyze the effectiveness of the implementation of the national exam in 2014 the level of school SMA Negeri (SMAN) by the Department of Education and the city of Palu. In the discussion of this study the effectiveness of using the theory being addressed by Robbins, consists of the application (1) The principle of suitability requirements, (2) The principle of the right target, and (3) The principle of benefit. This research is research that uses qualitative descriptive method approach. This study focused on the Department of Education and the city of Palu, addition this study conducted in several schools as representatives of State Senior High School in the city of Palu, SMAN 1 Palu, SMAN 3 Palu, and SMAN 5 Palu. In this study, other research informants purposively determined that as many as 5 people. Data collection techniques used were observation, interview, and documentation. The data analysis was performed with data reduction procedures, presentation of data and draw conclusions. The results of this study concluded that the effectiveness of implementation of the National Examination Level Senior High School by the Department of Education and Teaching Palu of Central Sulawesi Province, from 3 (three) element used in the present study, only elements of the principle of suitability needs not yet been reached with the good, because although National Examination budget already in budgeted but still feels less impacting on the lack of supporting infrastructure. Targeted principle has been reached with the good, although not yet reached the graduation of 100%, the implementation of the National Examination SMA has been done by purpose. And the principle has been reached with the good benefits, to improving the quality of output from every school in the Palu city and competence of existing educators.